Effects of muscarinic agents on chick choroids in intact eyes and eyecups: evidence for a muscarinic mechanism in choroidal thinning - Nickla, Debora L (2013)
PURPOSE: In chicks, ocular growth inhibition is associated with choroidal thickening and growth stimulation with choroidal thinning, suggesting a mechanistic link between the two responses. Because muscarinic antagonists inhibit the development of myopia in animal models by a non-accommodative mechanism, we tested the hypothesis that agonists would stimulate eye growth and thin the choroid. We also hypothesized that the effective growth-inhibiting antagonists would thicken the choroid. METHODS: Chicks, age 12–16 days, were used. In vivo: Agonists: Single intravitreal injections (20 µL) of oxotremorine (oxo), pilocarpine (pilo), carbachol (carb), or arecaidine (arec) were given to otherwise untreated eyes. A-scan ultrasonography was done prior to injections, and at 3, 24, 48 and 72 h. Antagonists: — 10D lenses were worn on one eye for 4 days. Atropine (atro), pirenzepine (pirz), oxyphenonium (oxy) or dicyclomine (dicy) were injected (20 µL) daily into lens-wearing eyes; saline injections were done as controls. Ultrasonography was done on d1 and on d4; on d4 measurements were done before and 3 h after injections. IN VITRO: Paired eyecups of retinal pigment epithelium (RPE), choroid and sclera were made from 1-week old chicks. All drugs except atropine were tested on one eyecup, its pair in plain medium. Choroidal thickness was measured at various times over 48 h. RESULTS: Agonists: In vivo, oxotremorine caused an increase in the rate of axial elongation (drug vs saline: 24–72 h: 338 µm vs 250 µrn; p < 0.001). All except pilocarpine caused choroidal thinning by 24 h (oxo, carb and arec vs saline: −25, −35 and −46 µm vs 3 µm). In vitro, all agonists thinned choroids by 24 h (oxo: −6 vs 111 µm; pilo: 45 vs 212 µm; carb: −58 vs 65 µm; arec: 47 vs 139 µm; p < 0.05). Antagonists: Atropine, pirenzepine and oxyphenonium inhibited the development of myopia in negative lens-wearing eyes, and also caused choroidal thickening (drug vs saline: 42, 80, 88 vs 10 µm per 3 h). In vitro, pirenzepine thickened choroids by 3 h (77 vs 2 µm, p < 0.01). CONCLUSIONS: Muscarinic agonists caused choroidal thinning in intact eyes and eyecups, supporting a role for acetylcholine in the choroidal response to hyperopic defocus or form deprivation. Only oxotremorine stimulated eye growth, which is inconsistent with a muscarinic receptor mechanism for antagonist-induced eye growth inhibition. The dissociation between choroidal thinning and ocular growth stimulation for the other agonists in vivo suggest separate pathways for the two.